Optogenetic identification of a rapid eye movement sleep modulatory circuit in the hypothalamus - Jego, Sonia; Glasgow, Stephen D; Herrera, Carolina Gutierrez; Ekstrand, Mats; Reed, Sean J; Boyce, Richard; Friedman, Jeffrey; Burdakov, Denis; Adamantidis, Antoine R (Nature neuroscience, 2013)
The authors find that optogenetic stimulation of melanin-concentrating hormone (MCH)-expressing neurons in the lateral hypothalamus selectively extends the duration of paradoxical sleep episodes in mice. Activation of MCH fibers in the tuberomammillary nucleus leads to the release of GABA and a similar increase in paradoxical sleep stability. Rapid-eye movement (REM) sleep correlates with neuronal activity in the brainstem, basal forebrain and lateral hypothalamus. Lateral hypothalamus melanin-concentrating hormone (MCH)-expressing neurons are active during sleep, but their effects on REM sleep remain unclear. Using optogenetic tools in newly generated Tg( Pmch - cre ) mice, we found that acute activation of MCH neurons (ChETA, SSFO) at the onset of REM sleep extended the duration of REM, but not non-REM, sleep episodes. In contrast, their acute silencing (eNpHR3.0, archaerhodopsin) reduced the frequency and amplitude of hippocampal theta rhythm without affecting REM sleep duration. In vitro activation of MCH neuron terminals induced GABA A -mediated inhibitory postsynaptic currents in wake-promoting histaminergic neurons of the tuberomammillary nucleus (TMN), and in vivo activation of MCH neuron terminals in TMN or medial septum also prolonged REM sleep episodes. Collectively, these results suggest that activation of MCH neurons maintains REM sleep, possibly through inhibition of arousal circuits in the mammalian brain.